Análise comparativa das metodologias de estudo exergoeconômico para um sistema de refrigeração por absorção de vapor de duplo efeito - Medeiros Neto, João Luiz de (2017)
The present work has the objective of presenting a comparative study of the exergic cost methodologies: Exergetic Cost Theory (TCE) and the Exergic Cost Specific (SPECO) - applied in the analysis of a series double-effect vapor absorption refrigeration system with distribution in a tower, which works with the pair of fluids, water (refrigerant) and lithium bromide (absorbing fluid), under development at the Institute of Sustainable Energies - IES, at the technology center of the Federal University of Paraíba. The thermodynamic analysis is done taking into account the energy and exergetic visions based on the first and second law of thermodynamics to obtain necessary information in the application of the ex-economic study. The application of the TCE method is based on the propositions developed by Valero and Lozano, and the SPECO method uses the principles of fuel (F) and product (P) diffused by the authors Lazaretto and Tsatsaronis as support. The economiceconomic study allocates the exergic and monetary costs associated with the exergy flows of the unit, as well as the decision on the optimization of the system's equipment. From the results obtained, through the two methods mentioned, an analysis of the differences and peculiarities of both was made. The absorption chiller under study consists of: two steam generators, condensation system, evaporator, absorber, expansion valves, solution pump and a heat exchanger. The computational code is developed, in EES (Solution of Engineering Equations) platform, due to the ease of obtaining the properties of the work fluids.